Improved cook stoves - India. Ministry of energy (New Delhi, 1986)
The National Programme on Demonstration of Improved Cookstoves (NPDIC) is widely and popularly Known in the country today. The programme is merely two years, old but it has reached the remotest villages in every district in the country. About a million improved stoves have been installed by now. Such a widespread programme needs a very strong technical back up to maintain the quality and to achieve the claimed benefits from the improved cookstoves, that is the saving of firewood, saving of cooking time, saving of time in cleaning the cooking pots, removal of smoke from the Kitchen, easy operation, less fire hazards, better hygiene, etc.
Keywords: Energy